International Maritime Labour Law - Carballo Piñeiro, Laura. author. aut Link
XIII, 326 p.
Keywords: This book focuses on maritime employment from a private international law perspective. The first chapter analyzes the background against which international jurisdiction and conflict of laws rules are drawn up and examines uniform law in this context, in particular the 2006 Maritime Labour Convention and the 2007 ILO Convention No. 188 on Work in Fishing. The second chapter addresses international jurisdiction issues as regards individual employment contracts, while also exploring other issues (e.g. insolvency-related and social security matters) that are subsequently revisited in the third chapter while discussing conflict of laws issues related to said contracts. In turn, chapter four focuses on collective labour relations and private international law, i.e. collective agreements, strikes and other forms of collective action and information, and on the participation rights of employees in business matters.